PELATIHAN PEMBELAJAR SUKSES MAHASISWA BARU UGM MELALUI KEGIATAN MENDONGENG UNTUK MENINGKATKAN RESPEK KEPADA LINGKUNGAN ANAK USIA 5-6 TAHUN: PELATIHAN PEMBELAJAR SUKSES MELALUI KEGIATAN MENDONGENG - Setianingtyas, Anna; anissa, nisa; setyawanti, dandang; julianto SN, arif; darmo, pujo; ratna W, Sukasih (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2022)
PPSMB 2021 aims to introduce UGM to the new students, which includes the history of phylosiphy and varios regulations in it. It also introduces UGM’s facilities and achievements. The activities which is done include completing various tasks with the theme of UGM identity building character, active role in society, adaptive and successful students, and finally real action for the community in the form of story telling activities to increase respect for the environment of 5-6 years old children. The result of the activities is can be concluded that UGM new students were able to increase the knowledge, self confidence, and empathy for early childhood. The participants of 5-6 years old children are experienced an increase in respect for the environment. In the final stage, the new students are able to carry out all the activities assigned by the committee and get a graduation assessment by the committee.